Selenium affects genes associated with immunity and apoptosis in in vitro follicles of ewes - Miranda-Jiménez, Leonor; López-Velázquez, María Monserrat; Quero-Carrillo, Adrián Raymundo; Robledo-Paz, Alejandrina (Austral Journal of Veterinary Sciences, 2024)
Selenium plays an important role in bodily functions. It activates immune cells such as neutrophils and immunity through T cells. However, its role in ovarian follicular gene expression has not been reported. The effects of selenomethionine (SeMet) on gene expression in in vitro ewe follicles and their relationship with immunity and apoptosis were studied. Preovulatory follicles were randomly cultured, and SeMet was added to the culture, followed by incubation for 24 h. Total RNA was extracted from follicles and placed on a microarray chip. Gene expression was analyzed using GenArise and classified using the DAVID v6.8 bioinformatics program based on the Gene Ontology and Kyoto Encyclopedia for Genes and Genomes (KEGG). Gene pathways were designed using Cytoscape v3.7.2. There were 2,538 differentially expressed genes (DEGs): 1,228 upregulated and 1,310 downregulated. The upregulated genes were classified into 32, 18, and 12 nodes related to biological processes, cellular components, and molecular functions, respectively. KEGG assigned these genes to 41 metabolic and signaling pathways. 94 genes were involved in eight pathways associated with immune processes. The expression levels of CD8, NFAT2, and CD48 were quantified using RT-qPCR. Selenium activated gene expression in the in vitro preovulatory follicles of ewes, some of which were related to the immune system. The relationship among CD8, NFAT2, and CD48 genes suggests a possible immune pathway related to follicular apoptosis regulation.